2011
DOI: 10.1161/circulationaha.111.052399
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Myocardial Fibrosis in Transgenic Mice With Targeted Overexpression of Tumor Necrosis Factor Requires Mast Cell–Fibroblast Interactions

Abstract: Background Transgenic mice with cardiac restricted overexpression of tumor necrosis factor (MHCsTNF mice) develop progressive myocardial fibrosis, diastolic dysfunction and adverse cardiac remodeling. Insofar as tumor necrosis factor (TNF) does not directly stimulate fibroblast collagen synthesis, we asked whether TNF-induced fibrosis was mediated indirectly through interactions between mast cells and cardiac fibroblasts. Methods and Results Cardiac mast cell number increased 2–3-fold (p < 0.001) in MHCsTNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 45 publications
1
69
0
Order By: Relevance
“…The proliferation of primary cardiac fibroblasts and NIH/3T3 fibroblast proliferation was determined by measuring bromodeoxyuridine (5-bromo-2′-deoxyuridine [BrdU]) incorporation as we have described previously,9 using a commercially available assay (Colorimetric Cell Proliferation ELISA, Roche). The fibroblast cell cultures were treated for 48 hours with PBS, NMC supernatants, or supernatants from necrotic liver cells (NLCs), heat-denatured NMCs and LMCs, NMCs and LMCs treated with DNase (0.5 μg/mL) or RNase (0.05 μg/mL), or 0.1 to 1000 ng/mL recombinant DAMPs (HMGB1 [Sigma-Aldrich], galectin-3 [R&D systems], IL-1α [Cell Signaling], S100β [Sigma-Aldrich], S100A8/A9 [ProSpec-Tany TechnoGene Ltd]) maintained in serum-free DMEM (Sigma-Aldrich), followed by the addition of BrdU for an additional 24 hours.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proliferation of primary cardiac fibroblasts and NIH/3T3 fibroblast proliferation was determined by measuring bromodeoxyuridine (5-bromo-2′-deoxyuridine [BrdU]) incorporation as we have described previously,9 using a commercially available assay (Colorimetric Cell Proliferation ELISA, Roche). The fibroblast cell cultures were treated for 48 hours with PBS, NMC supernatants, or supernatants from necrotic liver cells (NLCs), heat-denatured NMCs and LMCs, NMCs and LMCs treated with DNase (0.5 μg/mL) or RNase (0.05 μg/mL), or 0.1 to 1000 ng/mL recombinant DAMPs (HMGB1 [Sigma-Aldrich], galectin-3 [R&D systems], IL-1α [Cell Signaling], S100β [Sigma-Aldrich], S100A8/A9 [ProSpec-Tany TechnoGene Ltd]) maintained in serum-free DMEM (Sigma-Aldrich), followed by the addition of BrdU for an additional 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The α–smooth muscle actin (SMA) expression was determined by performing flow cytometric analysis of NIH/3T3 fibroblast cultures that had been stimulated for 48 hours with diluent or NMC supernatants (10 μg/mL), exactly as described earlier 9. The extent of α-SMA staining in the fibroblast cultures was expressed as the mean fluorescence intensity (MFI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 These studies demonstrated that sustained myocardial inflammation leads to temporal changes in the balance between MMP activity tissue inhibitor of matrix metalloproteinases (TIMPs) and mast cell-mediated TGF-β signaling. 30 Collectively, these time-dependent changes favor degradation of the extracellular matrix during the onset of inflammation and progressive myocardial fibrosis following sustained inflammation. Thus, the sustained activation of inflammatory signaling contributes to LV remodeling through a variety of different mechanisms that involve both the myocyte and non-myocyte components of the myocardium.…”
Section: Role Of Inflammation In the Pathogenesis Of Heart Failurementioning
confidence: 99%
“…5 The following primers were used for real-time polymerase chain reaction (PCR): collagen 1a1, forward primer 5 0 -CCAAGGGTAACAGCGGTGAA-3 0 and reverse primer 5 0 -CCTCGTTTTCCTTCTTCTCCG-3 0 ; collagen 1a2, forward primer 5 0 -TGTTGGCCCATCTGGTAAAGA-3 0 and reverse primer 5 0 -CAGGGAATCCGATGTTGCC-3 0 ; collagen 3a1, forward primer 5 0 -TCAAGTCTGGAGTGGGAGG-3 0 and reverse primer 5 0 -TCCAGGATGTCCAGAAGAACC-3 0 ; and GAPDH as internal control, forward primer 5 0 -AATGCATCC TGCACCACCAA-3 0 and reverse primer 5 0 -GTAGCCATATTC ATTGTCATA-3 0 (Integrated DNA Technologies, Coralville, IA, USA). 28 All quantity PCR reactions using SYBR Master Mix were performed on an ABI Prism 7000 sequence detector PCR system (Applied Biosystems, Foster City, CA, USA).…”
Section: Collagen Gene Expressionmentioning
confidence: 99%